Formulating the plastic deformation expression on coated substrate as a coating selection tool - Muniandy, Nagentrau (2017)
This study presents the investigation of elastic coating performance responses on elastic-plastic substrate of advanced alloys using Finite Element (FE) method with an explicit numerical algorithm under quasi-static condition. Cylinder-on-flat contact configuration subjected to a normal and tangential loading is examined. Two aeroengine materials, namely Ti-6Al-4V and Super CMV (Cr-Mo-V) alloys are employed. Coating mechanical properties which are applied load (500 N 1000 N), sliding displacement amplitude (0.005 mm - 0.12 mm), friction coefficient (0.3 - 0.9), coating elastic modulus (100 GPa - 400 GPa) and coating thickness (0.01 mm - 0.1 mm) are investigated. The effect of coating parameters on stress-strain distributions along with plastic deformation of the coated substrate are evaluated. The FE model is validated by comparing with theoretical Hertzian contact solution for homogeneous substrate, meanwhile coated substrate is validated by comparing with reported literature. The evolutions of contact pressure, von mises stress, equivalent plastic strain, tangential stress and surface profile are examined for various coating parameters. There is a clear increasing trend of development in stress-strain distributions along with plastic deformation, maximum pile-up and depth-in values with the increase in all coating parameters for both coated substrates ( except for coating thickness effect on Super CMV material, where the contradict trend is noted). Friction coefficient acts as the significant. coating parameter that leads to plastic deformation failure of coated substrate. The relatively higher stiffness and yield strength of the coated Super C.t\IV alloy registered limited plastic deformation compared to the coated Ti-6Al-4V allo_v. The coated substrate plastic defonnation marhernaJ.icc1l expressions are formulated according to the Lagrange mulr.ivariar.<" interpolation which can be used as an alternative method for FE approach. The weighted scoring method is practised in coating selection approach based 011 plastic deformation failure of coated substrate. The verified coating selection tool can contribute to knowledge in suitable material selection for coating based 0n its performance